2022
DOI: 10.3390/nu14020374
|View full text |Cite
|
Sign up to set email alerts
|

Whole Grain Consumption and Inflammatory Markers: A Systematic Literature Review of Randomized Control Trials

Abstract: Whole grain foods are rich in nutrients, dietary fibre, a range of antioxidants, and phytochemicals, and may have potential to act in an anti-inflammatory manner, which could help impact chronic disease risk. This systematic literature review aimed to examine the specific effects of whole grains on selected inflammatory markers from human clinical trials in adults. As per the Preferred Reporting Items for Systematic Reviews (PRISMA) protocol, the online databases MEDLINE, Embase, Cochrane, CINAHL, and Scopus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Previous research reported in the literature has shown that phenolics and antioxidant compounds fractionate differently between air‐classified coarse and fine fractions (Cammerata et al, 2021; Inglett & Chen, 2011). These compounds impart a range of potential health benefits to pulses and pulse‐based products, including reduced inflammation (Milesi et al, 2022) and lowering the risk of developing cardiovascular disease (Rangel‐Huerta et al, 2015) and diabetes (Charoensiddhi et al, 2022). However, there has been little attention given to the impact of air classification on these potential health‐benefitting compounds, with the primary focus being on production of protein and starch concentrates (Assatory et al, 2019; Fernando, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research reported in the literature has shown that phenolics and antioxidant compounds fractionate differently between air‐classified coarse and fine fractions (Cammerata et al, 2021; Inglett & Chen, 2011). These compounds impart a range of potential health benefits to pulses and pulse‐based products, including reduced inflammation (Milesi et al, 2022) and lowering the risk of developing cardiovascular disease (Rangel‐Huerta et al, 2015) and diabetes (Charoensiddhi et al, 2022). However, there has been little attention given to the impact of air classification on these potential health‐benefitting compounds, with the primary focus being on production of protein and starch concentrates (Assatory et al, 2019; Fernando, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…These may be partly responsible for the higher levels of obesity as reported by Rambaran et al (2018), where "the combined percentage of overweight and obese schoolchildren increased steadily from 12% in 2001 to 51.5% in 2018. High fruit, vegetable, and whole wheat/grain intake have been associated with decreased inflammation (Hosseini et al, 2018;Milesi et al, 2022), whereas inflammation has been linked to high carbohydrates (Karimi et al, 2021), saturated fats (Berg et al, 2020), protein, such as processed and red meats (Papier et al, 2022;Ley et al, 2014), sugar (Ma et al, 2022), and salt (Balan et al, 2020;Zhu et al, 2014). Pro-inflammatory (Khatun et al, 2021) foods are unhealthy and do not fit into the Mediterranean or cardiac diet (Richards, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…DF, “the seventh nutrient” of the body, is a component of fruits, vegetables, and whole grains, and is non-replaceable to maintain health [ 20 ]. DF has anti-inflammatory [ 10 ] and antioxidative properties [ 21 ] and has been shown to lower blood pressure [ 7 ], reduce serum cholesterol [ 22 ] and glucose levels [ 9 ], improve endothelial function [ 23 ], reduce body weight loss, aid favorable changes of gut microbial composition, and reduce the contact time between carcinogens and intestinal mucosal cells by increasing fecal bulking and viscosity [ 24 ]. All of these biochemical effects may be potentially related to a lower risk of chronic diseases and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…DF is primarily derived from plant-based foods, such as whole grain, seeds, vegetables, and fruits [ 6 ]. Various beneficial effects of fibers on serum low-density lipoprotein (LDL) cholesterol, blood pressure, insulin sensitivity, controlling body weight, and chronic inflammation may exert a protective effect on the cardiovascular system [ 7 , 8 , 9 , 10 ]. Indeed, previous studies have established that DF intake reduced the total mortality and CVD mortality in healthy populations [ 8 , 11 ] Accumulating observational studies indicates that DF is inversely associated with risk of hypertension, diabetes, dyslipidemia, peripheral vascular disease, and coronary heart disease [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%